PERILAKU BERBAHASA LATAH WARGA KECAMATAN TIRTAJAYA KABUPATEN KARAWANG PADA SEBUAH KAJIAN PSIKOLINGUISTIK - Andjanie Dwi Ayu Apriana; Hendra Setiawan (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Talkative speaking or Ekolalia is an attitude of imitating the speech or behavior of others. The cause of language disorders can be caused by environmental factors or anxiety experienced by a person. Talkative disorders are divided into five types, namely Ekolalia (talkative behavior or imitating what others say, Ecopraksia (talkative behavior by following other people's movements), Koprolalia (talkative behavior that pronounces genitals), Auto Ekolalia (talkative behavior that repeats words pronounced), and Automatic Obedience (spontaneous talkative behavior when surprised).This research uses the listen method and the cakap method. The listen method is used when researchers are interacting with sources or subjects by listening. Meanwhile, the cakap method is the method used when researchers go directly into the field and interact with the subject. Both methods are supported by several fishing techniques, record and record.The factors causing the language behavior of one of the residents of Pisangsambo Village, Tirtajaya District, are environmental factors consisting of suggestion, identification, imitation, and sympathy. Then, the factor is surprised by the words spoken by others outside the sufferer